Enhancing the Seventh Graders' Ability in Writing Descriptive Text Through Picture Media at Smp Negeri 2 Lolofitu Moi - Waruwu, Wince Lenta Viska Putri; Zega, Riswan; Telaumbanua, Kristof Martin Efori; Harefa, Trisman (Journal of English Language and Education, 2025)
This research aims to improve the descriptive text writing skills of seventh-grade students at SMP Negeri 2 Lolofitu Moi through the use of picture media. The background of this research is the students’ low ability in writing descriptive texts in accordance with structure and language rules. The research employed Classroom Action Research (CAR) with two cycles, each consisting of planning, action, observation, and reflection stages. The subjects were 20 seventh-grade students. Data were collected through observation, writing tests, and filed note, and were analyzed both qualitatively and quantitatively. The findings revealed that students’ writing skills improved from the first to the second cycle in terms of text structure, vocabulary, and grammar. The average writing score enhanced and exceeded the Minimum Mastery Criterion (KKM). Therefore, the use of picture media proved effective in enhancing the descriptive text writing skills of seventh-grade students at SMP Negeri 2 Lolofitu Moi